The role of polyadenylation in the induction of inflammatory genes - Gandhi, Raj D. (2017)
Polyadenylation is a universal step in the production of all metazoan mRNAs except histone mRNA. Despite being universal, previous experiments have implicated it in the regulation of inflammation. An inflammatory system using RAW 264.7 murine macrophage cells was established with bacterial lipopolysaccharide (LPS) used as a stimulus. After improving the poly(A) tail test (PAT) method of measuring poly(A) tail lengths, it was applied to inflammatory mRNAs during the inflammatory response. Poly(A) tail length was shown to vary over the course of the inflammatory response, and for Tnf, this was even true of initial poly(A) tail size, which is widely believed to be uniform for the majority of mRNAs. The adenosine analogue cordycepin (3’-deoxyadenosine) was shown to have anti-inflammatory effects on mRNA, in line with existing literature, and is likely to be the anti-inflammatory component of Cordyceps militaris ethanol extract. Inhibition of either import of cordycepin into cells or phosphorylation of cordycepin was sufficient to abolish its anti-inflammatory effects. Adenosine treatment led to repression of Il1b mRNA, but did not repress other mRNAs tested that were cordycepin-sensitive. This suggests that cordycepin does not simply act by mimicking the effect of adenosine, and that the two compounds have distinct modes of action. Inhibiting deamination of cordycepin potentiated its effects. We also observed that pre-mRNA levels of inflammatory genes were decreased by cordycepin treatment, indicative of effects on transcription. Other groups have reported that cordycepin interferes with NF-B signalling. As NF-B is an important transcription factor for the induction of inflammatory genes, this would provide a basis for explaining our observation that cordycepin represses at the transcriptional level. However, we did not observe any changes in NF-B signalling, with degradation of IB completely unimpeded by cordycepin treatment. Notably, cordycepin did shorten the Tnf poly(A) tail, and the observed inhibition of polyadenylation is consistent with observations that cordycepin led to decreased efficiencies of mRNA 3’ cleavage and transcription termination for Tnf. Such effects on polyadenylation and 3’ processing of mRNA were hypothesised to particularly affect unstable mRNAs that depend on longer poly(A) tails for avoiding decay and/or mRNAs with a high rate of transcription. However, comparison of microarray data to data from RNA-seq of RNA from 4-thiouridine labelling experiments showed that cordycepin-sensitivity did not correlate with mRNA stability or transcription rate. Long noncoding RNAs (lncRNAs) were found to be enriched in cordycepin-treated cells. If some of those lncRNAs have regulatory roles in inflammation, cordycepin’s effects may be mediated through them. Lastly, cordycepin significantly altered pain behaviour in a rat model of osteoarthritis (OA), supporting its continued use as a lead compound for exploration of new OA therapeutics.